Internationalization as a component of training programs for primary schools’ art disciplines teachers in China - Kalashnyk, Lyubov; Mkrtichian, Oksana (Educational Challenges, 2025)
Today, the People’s Republic of China views internationalization as a strategic national priority aimed at attracting the most advanced educational technologies to improve the quality of education in the country and showcasing its best pedagogical practices to the world. The article aims to explore the role and significance of internationalization in the preparation of art discipline teachers for primary schools in China, examining how the objectives and scope of such programs vary depending on the partner country, with a focus on their impact on fostering global competencies and cultural awareness. Additionally, the study introduces the concept of “home internationalization” into the Ukrainian academic discourse and highlights examples of real cooperation programs between China and other countries. Methodology. The research employs methods typical of general education and pedagogical comparative studies, including literature review, case studies, document analysis, and comparative analysis, which provide a comprehensive understanding of the issue under consideration. Results. The study identifies two main types of internationalization program. Programs targeting developed countries (e.g. the United States, the EU, Australia, and others) focus on participants learning advanced pedagogical methods and engaging in high-impact research. Programs with Asian countries (e.g. Singapore, Malaysia, and Japan) and economically dependent regions (African countries, Vietnam, Laos, and others) emphasise cultural exchange, equipping Chinese educators with certificates required for career advancement and showcasing China’s educational achievements. The concept of “home internationalization” describes initiatives with Taiwan, Hong Kong, and Macau, aimed at studying locally adapted European practices while demonstrating the advantages of China’s modern educational environment. Conclusions. The study concludes that internationalization is a transformative tool in the training of art teachers for primary schools, equipping them with innovative methodologies. By adapting program goals to the partner country, China effectively leverages internationalization to raise educational standards and address both domestic and global challenges. The findings illustrate the diversity and scale of these initiatives, offering valuable insights into how internationalization can contribute to the professional development of art teachers, including those specializing in primary school art disciplines, and promote cultural diplomacy.